Experimental study of intermeshed steel connections manufactured using advanced cutting techniques. (September 2020) - Shemshadian, Mohammad E.; Labbane, Ramzi; Schultz, Arturo E.; Le, Jia-Liang; Laefer, Debra F.; Al-Sabah, Salam; McGetrick, Patrick
Abstract: Advanced manufacturing techniques, such as plasma, waterjet, and laser can facilitate field assembly and disassembly of steel structural components, and therefore potentially transform how steel structures are designed and constructed. These techniques have opened up an opportunity to create a new class of steel connections that rely on intermeshed (i.e. interlocked) components in lieu of traditional connectors such as weld and bolt. This paper presents an experimental investigation on the mechanics of such intermeshed steel connections manufactured by high-definition plasma and waterjet cutting. Four full-scale specimens with an intermeshed connection were designed to resist gravity loading in steel frames. The experimental testing program focused on the behavior of intermeshed connections under vertical loads including pure flexural and combined flexural-shear loading. Both global load-deflection response and local deformation were measured to provide insights into the complex load transfer mechanisms. The experiments demonstrated ample load carrying capacity, approaching the beam plastic moment, and ample ductility, approaching a deflection over span length ratio of 1/60 to 1/40, through the interaction of individual components. Analysis of the test data also raises important questions that must be addressed for the practical design of these connections. Highlights: Advanced cutting techniques could help eliminate welding or bolting in steel connections. The intermeshed connection transfers loads through interlocking pieces. Waterjet and plasma cutting could meet the precision of the intermeshed connection. The intermeshed steel connection exhibits ample load carrying capacity and ductility. The angles and shear plates contribute in both moment and shear load transfer.